Studi Kasus Implementasi Metode Pembelajaran Aktif dalam Meningkatkan Keterampilan Berpikir Kritis Siswa Di Madrasah Ibtidaiyah - Tusyana, Eka (Tarunateach: Journal of Elementary School, 2025)
Active learning methods are crucial and transformative in improving students' critical thinking skills at Madrasah Ibtidaiyah (MI). This case study research aims to analyze the implementation of active learning methods and evaluate their contribution to improving students' critical thinking skills at the elementary level. Data was collected through triangulation of sources, namely interviews, observations, and documentation, to obtain a complete picture of practices in the field. The study results show that various factors influence the successful implementation of active learning methods. First, the main aspect is the facilitative role of teachers, which includes providing pedagogical support, optimizing the availability of relevant learning resources, and teachers' ability to respond to student dynamics and feedback. Additionally, an inclusive and supportive learning environment is essential, creating an atmosphere where every student feels welcome and valued, significantly encouraging increased engagement and motivation for their learning. Second, the improvement of students' critical thinking skills is also strongly influenced by the internal characteristics of the students themselves, including the level of initial critical thinking ability, the strength of their intrinsic motivation to learn, and their confidence in expressing opinions. Therefore, this study concludes that successfully implementing active learning requires synergy between adaptive teacher teaching strategies and a deep understanding of students' psychological conditions and early cognitive abilities.